The Influence of Layout and Warehouse Management System on the Effectiveness of Warehouse Management at PT BGR Logistik Indonesia, Semarang Regional Division - Avrillia Kharisma Puspitasari Prias; Nurul Imani Kurniawati (Universitas Diponegoro, 2025)
This study aims to analyze the influence of warehouse layout and Warehouse Management System on the effectiveness of warehouse management at PT BGR Logistik Indonesia Divre Semarang. The problem arises from a warehouse layout that does not meet operational standards and the suboptimal implementation of WMS, leading to stock recording errors and decreased operational efficiency. This research employs a quantitative approach using a survey method. The population includes all employees in the Warehouse Division of PT BGR Logistik Indonesia Semarang Branch, with a sample of 35 respondents selected through a saturated sampling technique. Data were collected using questionnaires with a Likert scale of 1–5 and analyzed using simple and multiple linear regression through SPSS version 25. The results show that both warehouse layout and Warehouse Management System have a positive and significant influence on the effectiveness of warehouse management, both partially and simultaneously. The coefficient of determination (R²) of 86.5% indicates that the two independent variables together explain the majority of the variance in warehouse management effectiveness. This study offers novelty by examining the simultaneous integration of digital warehouse management systems and physical layout planning, as well as highlighting their impact on work effectiveness within the logistics company context. These findings emphasize the importance of synergy between technical aspects and information systems in supporting efficient and accurate warehouse operations.